Frequency of oligosymptomatic gastrointestinal tract diseases and its relation to insulin-like growth factor I in idiopathic (non-GH-deficient) short stature children - Renata Stawerska; Marzena Kolasa-Kicińska; Michał Kolejwa; Joanna Smyczyńska; Maciej Hilczer; Elżbieta Czkwianianc; Andrzej Lewiński (Archives of Medical Science, 2020)
Introduction There is a discussion about growth hormone therapy in idiopathic short stature (ISS) children. To diagnose ISS, it is necessary to exclude other diseases; gastrointestinal tract diseases (GIDs) are among them. However, GID symptoms may be scarce. The aim of the study was to evaluate the frequency of unexpected oligosymptomatic GIDs in ISS and assess their influence on auxological parameters and insulin-like growth factor I (IGF-I) concentration.